Estimating an effect by nature conservation perspectives of a future remediation in a landfill nearby kiskunhalas - Kende, Zoltán (JOURNAL OF LANDSCAPE ECOLOGY, 2013)
In this article I would like to answer that question, what will happen, if the landfill nearby Kiskunhalas was to be remediated? For the correct answer I make several examinations which included landscape change study and coenological survey too. The remediation of the closed landfill can be made by the financial resource which the council of Kiskunhalas won in a Hungarian KEOP fund. For the examination of the landscape changes I used several military surveys and topographic maps from the past, and the area’s ortophotos from the years of 2000, 2005, 2009. The coenological survey was made by the BRAUN-BLANQUET 2X2 m quadrate method and the results are shown in diagrams. From my research results I try estimating the remediation effects by nature conservation perspectives, and formulate some monitoring and biomonitoring tasks which can establish another researches and examinations in the future. My results will be good for the study area’s nature conservation and ecological inspections of the remediation for the next 5–10 years.